Reproductive Capacity, but not Food Consumption, is Reduced by Continuous Exposure to Typical Genotoxic Stressor γ‐Rays in the sentinel species Gammarus fossarum - Frelon, Sandrine; Recoura‐Massaquant, Rémi; Dubourg, Nicolas; Garnero, Laura; Bonzom, Jean‐Marc; Degli‐Esposti, Davide (Environmental toxicology and chemistry, 2024)
Abstract The long‐term impacts of radiocontaminants (and the associated risks) for ecosystems are still subject to vast societal and scientific debate while wildlife is chronically exposed to various sources and levels of either environmental or anthropogenic ionizing radiation from the use of nuclear energy. The present study aimed to assess induced phenotypical responses in both male and female gammarids after short‐term continuous γ‐irradiation, acting as a typical well‐characterized genotoxic stressor that can interact directly with living matter. In particular, we started characterizing the effects using standardized measurements for biological effects on few biological functions for this species, especially feeding inhibition tests, molting, and reproductive ability, which have already been proven for chemical substances and are likely to be disturbed by ionizing radiation. The results show no significant differences in terms of the survival of organisms (males and females), of their short‐term food consumption which is linked to the general health status (males and females), and of the molting cycle (females). In contrast, exposure significantly affected fecundity (number of embryos produced) at the highest dose rates for irradiated females (51 mGy h–1) and males (5 and 51 mGy h–1). These results showed that, in gammarids, reproduction, which is a critical endpoint for population dynamics, is the most radiosensitive phenotypic endpoint, with significant effects recorded on male reproductive capacity, which is more sensitive than in females. Environ Toxicol Chem 2024;43:2071–2079. © 2024 SETAC